PARTISIPASI SISWA MENGGUNAKAN METODE STUDI KASUS PADA PELAJARAN GEOGRAFI - Pratiwi, Ika Cahya; Nofrion, Nofrion (JURNAL BUANA, 2024)
This study aims to determine student participation in learning using the case study method in geography lessons at SMA Pertiwi 1 Padang This research is a descriptive study using a quantitative approach with a sampling technique that is random sampling with a sample of class XII semester I with a population of class XII social studies students. SMA Pertiwi 1 Padang, Data collection techniques through observation with descriptive quantitative techniques. Data analysis using the Percentage Technique. The results of this study were to determine that student participation in learning using the case study method in SMA Pertiwi 1 obtained data with an achievement level of 68% in the mediumcategory.